Plasma pressure broadening for few-electron emitters including strong electron collisions within a quantum-statistical theory - Lorenzen, S.; Omar, B.; Zammit, Mark; Fursa, Dmitry; Bray, Igor (The American Physical Society, 2014)
To apply spectroscopy as a diagnostic tool for dense plasmas, a theoretical approach to pressure broadening is indispensable. Here, a quantum-statistical theory is used to calculate spectral line shapes of few-electron atoms. Ionic perturbers are treated quasistatically as well as dynamically via a frequency fluctuation model. Electronic perturbers are treated in the impact approximation. Strong electron-emitter collisions are consistently taken into account with an effective two-particle T-matrix approach. Convergent close-coupling calculations give scattering amplitudes including Debye screening for neutral emitters. For charged emitters, the effect of plasma screening is estimated. The electron densities considered reach up to ne=1027 m-3. Temperatures are between T=104 and 105 K. The results are compared with a dynamically screened Born approximation for Lyman lines of H and H-like Li as well as for the He 3889 Å line. For the last, a comprehensive comparison to simulations and experiments is given. For the H Lyman-a line, the width and shift are drastically reduced by the Debye screening. In the T-matrix approach, the line shape is notably changed due to the dependence on the magnetic quantum number of the emitter, whereas the difference between spin-scattering channels is negligible.